The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1007/s00253-008-1683-z
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of puerarin into its 7-O-glycoside derivatives by Microbacterium oxydans (CGMCC 1788) to improve its water solubility and pharmacokinetic properties

Abstract: Microbacterium oxydans strain NJ 6 isolated from soil samples converted puerarin into two novel compounds, puerarin-7-O-glucoside and puerarin-7-O-isomaltoside, via an unreported O-glycosylation of the phenolic hydroxyl group at the 7-position of puerarin. Sucrose, maltotriose, and maltose could be used as glucosyl donors for glycosylation of puerarin, but uridine-diphosphate glucose, glucose, fructose, lactose, cyclodextrin, and starch could not. Regardless of the position of B-ring in the (iso)flavonoids cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 11 publications
1
38
1
1
Order By: Relevance
“…We have previously reported that puerarin is transformed to two products, puerarin-7-O-glucoside and puerarin-7-O-fructoside, when it is transformed by free enzyme or bacterial cells permeabilized with organic solvent (Jiang et al, 2008;Yu et al, 2010). However, we showed that the main transformation product by immobilized puerarin glycosidase is puerarin-7-O-glucoside.…”
Section: Discussioncontrasting
confidence: 44%
See 3 more Smart Citations
“…We have previously reported that puerarin is transformed to two products, puerarin-7-O-glucoside and puerarin-7-O-fructoside, when it is transformed by free enzyme or bacterial cells permeabilized with organic solvent (Jiang et al, 2008;Yu et al, 2010). However, we showed that the main transformation product by immobilized puerarin glycosidase is puerarin-7-O-glucoside.…”
Section: Discussioncontrasting
confidence: 44%
“…However, the transformation by resting cells is limited by low transformation efficiency and long transformation time because extracellular puerarin diffuses slowly into the intracellular space through the barrier of the cell membrane. When the intracellular puerarin reaches a certain concentration, it is transformed by M. oxydans CGMCC 1788 glycosidase to glycosylated puerarin that is then secreted through the cell membrane to the extracellular solution (Jiang et al, 2008;Yu et al, 2010). In order to increase the transformation efficiency and shorten the transformation time, free glycosidase extracted from disrupted cells of M. oxydans CGMCC 1788 has been used to transform puerarin (Yu et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…이런 문제점은 폴리페놀의 당화과정 (glycosylation)을 통하여 합성된 배당체를 이용하여 극복할 수 있다. 배당체의 합성은 화학적 방법으로 가능하지만, 이런 방법은 고온, 고압을 포함하는 조건이 필수적이고 합성된 아 노머(anomer) 물질의 분리 및 환경문제 등을 야기하여 [18] 최 근에는 생물체가 지니는 당 전이 능력을 갖는 효소를 이용한 당 전이 반응(transglycosylation)을 통하여 빠르고 쉽게 생산 하고 있다 [8,13] (Fig. 2).…”
Section: 서 론unclassified